Impacto da distância social na aceitabilidade do comportamento disfuncional do consumidor - Tomazelli, Joana Boesch (2020)
This study contributes to the theoretical deepening of the phenomenon of Dysfunctional Consumer Behavior (DCB), which is not yet consolidated in the Marketing literature (Kang & Gong, 2019). As there were no reports of studies of the DCB phenomenon supported by Construal Level Theory (CLT), this study also seeks to fill this theoretical gap. The main objective of this study is to relate DCB to the psychological distance between the person responsible for a failure and the consumer. Discussions are also provided on the acceptability of the DCB in face of the already established Attributional Theory, since the controllability had not been verified as a moderator in a relationship whose acceptability of the DCB is the dependent variable. In view of the relationship between social distance and the acceptability of the DCB, this research argues that the Attributional Theory and the nature of the phenomenon itself has an interference role in the acceptability of the DCB. Therefore, a sequence of three experimental studies was carried out with consumers recruited via Prolific, to test six hypotheses. In the first study, as a result of testing the main effect, social distance impacts the acceptability of the DCB, so that if the distance is perceived as socially distant, it will result in greater acceptability of the DCB. As an explanatory mechanism for this main effect, the results revealed mediation by trust. In the second study, it was found that controllability moderates the relationship between social distance and DCB acceptability. In the third study, it was identified that the nature of the DCB moderates the effect of the social distance between the agent and the consumer on the acceptability of the DCB. Moderate mediation by guilt was also found in the relationship between social distance and DCB acceptability. Academic and managerial implications are presented at the end of this report, along with opportunities for future research.